Recovery of Natural Folic Acid and It’s Identification as Protein Isolate Through Beans Extraction Fermented by Rhizopus sp. and Rhizopus oligosporus C1 for Smart Food Formula - Agustine Susilowati; Aspiyanto Aspiyanto; Puspa D. Lotulung; Hakiki Melanie; Yati M (Institut Teknologi Sepuluh Nopember, 2017)
Protein isolate produced through fermentation of soy beans (Glycine soja L.), mung beans (Phaseolus radiatus L.) and kidney beans (Phaseolus vulgaris L.) using fungi of Rhizopus sp. (mixture) or Rhizopus oligosporus C1 (single) are natural source of folic acid for formulation of smart foods. The objective of this experimental activity was to know potential use of fermented beans (tempeh) as protein isolate as a result of pulverizing process and filtration through 100 mesh sieve and characteristic of its monomer, particularly glutamic acid as a part of folic acid via LC-MS. Protein isolate extract was generated via pulverizing mixture between soy tempeh, mung bean tempeh and kidney bean tempeh, and water with ratio of 1 : 1, 1 : 2, 1 : 3, 1 : 4 and 1 : 5, respectively followed by filtration through 100 mesh sieve. The result of experimental activity displayed that interaction of all treatments affected on composition of tempeh extraction result as protein isolate. Identification using LC-MS showed that difference in relative intensity for 3 kinds of tempeh on presence of glutamic acid. Protein isolates from soy tempeh, mung bean tempeh and kidney bean tempeh produced domination of glutamic acid monomer indicated subsequently at chromatogram with T 4.1, T 5.7 and T 7.1; T 4.0 and T 3.9.